The Effect of Intellectual Capital on the Performance of Financial Services Companies Listed on the Indonesia Stock Exchange - Muhammad zidane; Dina Patrisia (Financial Management Studies, 2022)
The purpose of this study is to analyze the power of intellectual capital performance of financial services listed on the Indonesian financial market before the outbreak and during the epidemic This study is a causative study. The population in this study is all monetary service companies listed on the Indonesian impact market. Meanwhile, the illustrations in this study were determined using a porposive sampling system with the following criteria: a) listed on the IDX during the observation period (2019-2020) b) the company publishes payment of fees during the observation period, resulting in 60 illustrations with a total of 120 observations. the category of data used is subordinate data received from www. Idx.co.id. the system that is used is a multiple regression view with a level a of 5%. From the results received, it can be concluded that intellectual capital (value added intellectual coefficient TM) positively affects the appearance of the partnership (return on equity) on the monetary service partnership listed on the IDX with a significant price in 2019 or before the outbreak, which is 0.006 <0.05 while it was in 2020 or the epidemic period, there was a decrease even though intellectual capital (value added intellectual coefficient TM) affected the appearance of the joint venture with a significance price of 0.021 <0.05 and if the illustration was combined between 2019-2020 intellectual capital (value added intellectual coefficient TM) affected the appearance of the joint venture with significance price 0.000<0.05